PENGARUH PENYULUHAN PAJAK, KUALITAS PELAYANAN PAJAK, DAN TINGKAT KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN (Studi Empiris terhadap Kantor Pelayanan Pajak Pratama Batu) - Nila Wardhani Hermianti Putri; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to determine the effect of tax counseling, the quality of tax services, and the level of awareness of corporate taxpayer compliance. Researchers determined that corporate taxpayers who are actively registered at the Pratama Batu Tax Office are the population. Meanwhile, the researchers used probability random sampling technique in taking the sample, and to determine the number of samples using the Slovin formula with the results of 98 respondents. This research is classified as quantitative research with primary data obtained from distributing online questionnaires to respondents, as well as secondary data obtained from documents or literature. The method of data analysis was carried out by multiple linear regression analysis. Using SPSS 16.0 for windows. The results of this study indicate that tax counseling, tax service quality, and level of awareness have a significant effect on corporate taxpayer compliance either partially or simultaneously.Keywords: Tax Counseling, Tax Service Quality, Awareness Level, and Taxpayer Compliance.